EVALUASI KONSEP LOKALISASI PENGADAAN KOMPONEN DENGAN PENDEKATAN TOYOTA BUSINESS PRACTICE (TBP) - Novie Susanto; Deshtyan Erlangga Adi (Universitas Mercu Buana, 2017)
Abstract. This study aims to evaluate the deviation between planned Cost of GoodsManufacturing with actual Cost of Goods Manufacturing (COGM) in PT. TMMIN thatexceeding 10%. The obtained priority issues is the procurement of Spring Guide Set DBAGS-Dcomponent. A localization activity is designed against Spring Guide Setcomponent procurement through several local suppliers, namely PT. HMI, PT. IT, andPT. JAPM. The analysis includes three aspects: cost, delivery time, and quality. ToyotaBusiness Practice (TBP) is applied in this study. Toyota Business Practice is a problemsolving method that consists of eight steps ranging from problem identification,determination of the root of the problem to the standardization activities. In the TBP,some calculations costs through cost estimation analysis approach and calculation ofdepreciation using the Sum of the Year Digits is taken into account. Throughlocalization activity, it is expected the import costs in the procurement of componentscan be reduced, in line with expected delivery and quality aspects. The results show therecommendations of selected supplier are PT. IT for then negotiated the cost reductionand PT. JAPM for quality improvement of the products offered.